2017
DOI: 10.1371/journal.pone.0181351
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine used as a perineural adjuvant to ropivacaine, does not prolong the duration of sensory block when controlling for systemic effects: A paired, blinded, randomized trial in healthy volunteers

Abstract: BackgroundClonidine used as an adjuvant to ropivacaine have been shown to prolong the duration of peripheral nerve blocks. The mechanism of action remains unclear. We hypothesized, that clonidine used as an adjuvant to ropivacaine extends the duration of an adductor canal block (ACB) by a peripheral mechanism, compared to ropivacaine alone when controlling for systemic effects.MethodsWe conducted a paired, blinded, randomized trial in healthy volunteers. Participants received bilateral ACBs containing 20 ml ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(55 reference statements)
0
2
1
Order By: Relevance
“…In that study, however, they used 2.5 mL of 0.75% ropivacaine solution; we used 2.5 mL of 0.2% ropivacaine solution, so we achieved a prolonged effect with lower concentration and volume. In the study by Andersen et al (14), the mean duration of the adductor canal block using 20 mL of ropivacaine 0.5% was 19.3 hours, but the concentration of solution was not similar with our patient. In Gonzalez et al ( 15), 4 genicular nerves (superior medial, superior lateral, inferior medial, and inferior lateral) Nerve Palsy & Ropivacaine Duration after Inferolateral Genicular Nerve Block were blocked with 4 mL of bupivacaine 0.25%; they reported a lower pain score and rescue analgesia findings, which is similar to our study with respect to the decrease in pain score; however, we observed a prolonged anesthesia with diluted ropivacaine in the common peroneal nerve, which is located next to the genicular nerve.…”
Section: Discussioncontrasting
confidence: 71%
“…In that study, however, they used 2.5 mL of 0.75% ropivacaine solution; we used 2.5 mL of 0.2% ropivacaine solution, so we achieved a prolonged effect with lower concentration and volume. In the study by Andersen et al (14), the mean duration of the adductor canal block using 20 mL of ropivacaine 0.5% was 19.3 hours, but the concentration of solution was not similar with our patient. In Gonzalez et al ( 15), 4 genicular nerves (superior medial, superior lateral, inferior medial, and inferior lateral) Nerve Palsy & Ropivacaine Duration after Inferolateral Genicular Nerve Block were blocked with 4 mL of bupivacaine 0.25%; they reported a lower pain score and rescue analgesia findings, which is similar to our study with respect to the decrease in pain score; however, we observed a prolonged anesthesia with diluted ropivacaine in the common peroneal nerve, which is located next to the genicular nerve.…”
Section: Discussioncontrasting
confidence: 71%
“…6 However, in the context of prolongation of analgesic effect and reduction of opioid rescue dosage, the addition of clonidine (150 mcg) to ropivacaine has been observed to be unhelpful during brachial plexus block 10 and adductor canal block. 11 Addition of dexmedetomidine has been found to prolong the duration of SCBP block of bupivacaine by 8 h 12 and that of ropivacaine by 4 h. 13 Dexmedetomidine as adjuvant to ropivacaine for ulnar nerve block was found to prolong the analgesia by about 200 min. 14 Hence, it appears that clonidine and dexmedetomidine both as adjuvant to bupivacaine for use in SCBP blocks have been found to prolong sensory as well motor blockade when combined individually.…”
Section: Clonidine and Dexmedetomidine As Adjuvant To Ropivacaine For...mentioning
confidence: 99%
“…9 Ropivacaine and bupivacaine have similar analgesic effect when used for peripheral nerve blocks. 10 Adjunct medications added to peripheral nerve blocks to augment duration of action such as epinephrine, 1,5 buprenorphine, 11 clonidine, [12][13][14] dexmedetomidine, 15 and dexamethasone 16,17 yielded unsatisfactory or conflicting results, with some carrying additional side effects such as increased nausea, vomiting, bradycardia, and hypotension.…”
mentioning
confidence: 99%